Artificial Intelligence & Deep Learning: Pet and Spect Imaging and Classification on Brain MRI Images List. Issue 1 (1st August 2022) - Goel, Amit Kumar; Yadav, Sagar; Zubair,; Jain, Naman
Abstract: Cognitive abilities commonly linked with human brains include learning and problem solving. Another option is just a preprogrammed rule that instructs the computer to perform a given action under specified circumstances. Voice recognition and image recognition, for instance, are both widely used in daily life and may be found everywhere. "Deep learning" (DL) approaches, in particular, due to their ability to come up with creative solutions to complex situations throughout the past decade. Both cancerous and non-cancerous tumors can be seen in the human brain (benign). Google developed the open-source deep learning library Tensor Flow. It can be combined with traditional machine learning. It was created on top of PIL that the Python Pillow module exists (Python Image Library). This collection of modules is critical to Python's ability to perform image processing. "A deep learning API developed in Python" is powered by "the TensorFlow-based machine learning platform TensorFlow." NumPy is a Python library for manipulating arrays, as the name suggests. Also included are linear algebra, the Fourier transform, and matrix functions. As far as the ResNet50 model goes, it has 48 convolutional layers, a maxpool and an averagepool layer. Up to a scale of 3.8 x 109, floating point operations can be performed. ResNet-50 is a type of neural network with 50 layers. You can import a pre-trained version of the network from the ImageNet database.